ANALYSIS OF STUDENTS’ DIFFICULTIES IN SOLVING STORY PROBLEMS ON LINEAR PROGRAMMING MATERIAL AT SMAN 3 SIDRAP - Tiara; Usman; Muhammad Ahsan (Jurnal Prinsip Pendidikan Matematika, 2021)
This study aims to describe students' difficulties in solving story problems on linear programming material, the factors that cause students' difficulties in solving story problems, and how to overcome students' difficulties in solving story problems on linear programming material at SMAN 3 SIDRAP. This type of research is descriptive qualitative, with the research subject being class XI IPS 2 SMAN 3 SIDRAP, totalling ten students. Based on the results of the research, the difficulties experienced by students in solving story problems on linear programming material are conceptual difficulties, principle difficulties, information difficulties and arithmetic difficulties. Factors causing difficulties are divided into external factors, including the family and school environment and internal factors, including the lack of student interest in learning mathematics, especially in linear programming material, study routines, and lack of motivation to learn. Efforts were made to overcome these difficulties, namely providing a good understanding to students, making students active in asking questions and using learning media.